Analisis Strategi Pelayanan Geriatri Berbasis Rumah Sakit dengan Menggunakan Value Chain di Rumah Sakit Islam Kendal - Sutanti Murti Handayani; Sudiro Sudiro; Ani Margawati (Jurnal Manajemen Kesehatan Indonesia, 2016)
An increasing number of elderly peopel in Kendal district led to a rise in RSI Busines Plan of geriatric services have not been clearly superior to the Kendal geriatric patients but has not been served in a holistic manner. analysis of value chain in the pre service, point service, and after service in order to provide added value to the service as a competitive relevance as an input in determining the business strategy. The purpose of the study to analyze the application value chain strategies to service-based outpatient geriatric hospital in Kendal RSI. The research is a qualitative with depth interview techniques. The subjects of the study consisted of four main informants is Director, Service Manager, HR Manager, Head of Outpatient Installation, while two specialist doctors, one of interna’s nurse and one of nurse In Neural’s poli as informant triangulation. The results showed that the strength of the value of the services geriatrics is at the geographical location, service satisfaction, quality of service, supported by a professional culture and technology resources for class C. The weakness lies in the value of nurses who have not been standardized service providers as a nurse gerontik and lack of care of the elderly market surveys. Care of the elderly is still served in outpatient poly and physiotherapy. The process of competitive analysis on the relevance of the idea that the care of the elderly has a value that is greatly appreciated, rare, difficult to imitate and sustainable. Conclusions This study is the care of the elderly have a competitive advantage and strategies that can be applied is differentiation. It is recommended to management to evaluate busines plan to conduct market research and marketing planning of human